Faktor-Faktor Yang Memengaruhi Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi - Viriany, Tiffany Wijaya, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study is conducted to find the influence of profitability and company growth on firm value with capital structure as moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. The sampling method of this study is purposive sampling to obtains 33 manufacturing companies and 132 sample data. Analysis techniques used in this study are multiple linear regression and moderated regression analysis (MRA). This study used Eviews 12.0 to analyze panel data of this study. The results showed that profitability has a significant positive effect on firm value, but the company growth did not significantly affected the firm value, while capital structure as moderating variable is does not able to moderate profitability and company growth effect on firm value.